Digital Marketing’s Influence on Consumer Purchasing Decision: A Case Study in Iraq - Sukaini, Ali Khalaf Mohammed Al (Journal of Asian Multicultural Research for Social Sciences Study, 2022)
Examining the effects of digital marketing on customer purchase decisions was the main goal of this study.Specific objectives guided the study, including the evaluation of digital marketing platforms in Iraq with the ability to impact purchasing decisions and the identification of product categories that customers purchased on digital media platforms. Although the corporation is not completely responsible for the purchase choice process of consumers, It is a comprehensive procedure that takes into account psychological aspects, social influence, word-of-mouth, cultural values, and financial level. A total of 250 questionnaires were delivered, with the exclusion of the unfinished surveys, and 220 usable samples were obtained, yielding an overall response rate of 88%. Multiple regressions, reliability tests, correlation tests, and descriptive analysis were all employed in this study. The findings of this study also demonstrated the major effect of digital marketing on customer purchase decisions, including social media marketing and mobile marketing. Hypothesis testing, however, showed that various well-known digital marketing platforms in Iraq had an impact on students’ behavior. Through digital media platforms, students in Iraq make purchases across a wide range of product categories, and digital marketing has an impact. In the end, firms need to implement plans to harness the digital world and technology as well as raise brand recognition through online media in order to compete in today’s business climate.